Selective anodic transformation of glycerol with ZnCo 2 O 4 2D nanoplates: sustainable coproduction of carbon-negative green hydrogen and formic acid - Saha, Arindam; Murugiah, Vasantharadevi; Kollenteakathootu, Jayalakshmi; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2025)
In the pursuit of sustainable green hydrogen production, the electrooxidation of abundantly available carbon-containing molecules at a significantly low voltage presents a promising pathway, helping to reduce the cost of hydrogen generation while simultaneously yielding value-added chemicals/fuels. In the current study, we report the template-free green synthesis of ZnCo2O4 directly on Ni-foam (NF), demonstrating anodic stability and bifunctional electrocatalytic activity toward alkaline (1 M KOH) glycerol oxidation over an extended duration of 230 h at 50 mA cm- 2. The catalyst's high electrochemical surface area contributes to its remarkable performance, enabling sustained high current density. Compared with monometallic (ZnO or Co3O4) oxides, ZnCo2O4 oxide reveals superior catalytic performance. The two-electrode electrolyzer setup (ZnCo2O4 oxide/NF || ZnCo2O4 oxide/NF) operates at a significantly low cell potential of 1.9 V to achieve 100 mA cm- 2 in 0.2 M glycerol, which is 180 mV lower than that of conventional 1 M KOH solution. The three-electrode setup achieved 1 A/cm2 current density at 1.907 V vs RHE. Both anodic and cathodic processes exhibit high Faradaic efficiency, achieving 98% efficiency for H2 and 90% selectivity toward formate generation, along with significant methanol production. This demonstrates efficient C-C bond cleavage capability with glycerol to predominantly C1-products. The electrocatalytic formate production from alkaline glycerol using ZnCo2O4 offers an energy-efficient pathway, facilitating carbon-negative green hydrogen generation, thus contributing to a cleaner and sustainable energy landscape.
Keywords: energy conversion; Formic acid; glyceroloxidation; green H-2; water electrolysis